International Faculty Mobility: Crucial and Understudied - Rumbley, Laura E.; de Wit, Hans (International Higher Education, 2017)
Increased global competition not only implies that universities must compete for the best and brightest of undergraduate and graduate students, but they must also seek out talented researchers and teachers on a worldwide scale. The international mobility of faculty is also important in relation to the internationalization of higher education. Yet, the scope and nature of international mobility of faculty is a rather unknown and understudied phenomenon. This article addresses definitional and contextual issues, and national, institutional and individual factors related to international faculty mobility, and calls for more research on the phenomenon.